Efficacy of Local Drug Delivery Agents as an Adjunct to Scaling and Root Planing for Treating Furcation Defects in Chronic Periodontitis - A Systematic Review Protocol - Baliga, Vidya; Baliga, Sudhindra; Oza, Ranu; Sharma, Varsha; Khatib, Mahalaqua Nazli (International Journal of Psychosocial Rehabilitation, 2020)
Periodontal disease is a chronic inflammatory disease initiated by dental plaque. Periodontitis affects the periodontium as a whole. It leads to destruction of alveolar bone and ultimately tooth loss. Chronic periodontitis affects the root trunk of multirooted teeth commonly leading to furcation defect. Pharmacologic management of chronic periodontitis is used as an adjunct to conventional scaling and root planing (SRP). It includes chlorhexidine mouth rinses, subgingival irrigation and local drug delivery agents. Potential therapeutic agents such as non-steroidal anti‑inflammatory drugs, chemically modified tetracyclines, and bisphosphonates to treat bone resorption are well documented in periodontal literature. However, the role of local drug delivery agents (LDD) as an adjunct to scaling and root planing needs further exploration and research. The aim of this systematic review will be to determine the efficacy of the currently available local drug delivery agents as an adjunct to scaling and root planing for the treatment of furcation defects in chronic periodontitis